Perancangan Aplikasi Virtual Reality 360 Berbasis Web di Universitas Advent Indonesia - Sozanolo Gea; Raymond Maulany (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
Today, many web applications are dynamic and interactive to be applied in Information Systems, Telecommunications, Trade, Banking, Education and various other types. Along with these developments. The author wants to create UNAI Virtual Reality which aims to help website visitors see the UNAI campus more closely. The objectives of this study are: (1) Creating a Virtual Reality 360o for Adventist University of Indonesia. (2) Presenting 360o images through the website of the Adventist University of Indonesia. (3) Making visitors to the Adventist University website Indonesia more easily recognize the location and environment around UNAI which is presented in a Virtual form. The conclusions from this study are: (1) The Virtual Reality 360o application can be implemented on the website of the Adventist University of Indonesia. (2) The Virtual Reality 360o application is interesting, interactive and easy to use, making it easier for users to obtain information about the UNAI environment. The method used in designing this virtual reality application uses the waterfall development model. Method of developing a waterfall system. The SDLC model of waterfall is often also called a linear sequential model. The application designed can display 360 images from several corners of the campus in interactive web forms.